2022
DOI: 10.1038/s41598-022-22035-0
|View full text |Cite
|
Sign up to set email alerts
|

Protection of insect neurons by erythropoietin/CRLF3-mediated regulation of pro-apoptotic acetylcholinesterase

Abstract: Cytokine receptor-like factor 3 (CRLF3) is a conserved but largely uncharacterized orphan cytokine receptor of eumetazoan animals. CRLF3-mediated neuroprotection in insects can be stimulated with human erythropoietin. To identify mechanisms of CRLF3-mediated neuroprotection we studied the expression and proapoptotic function of acetylcholinesterase in insect neurons. We exposed primary brain neurons from Tribolium castaneum to apoptogenic stimuli and dsRNA to interfere with acetylcholinesterase gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 80 publications
(123 reference statements)
1
2
0
Order By: Relevance
“…Current knowledge suggests that complex regulation of apoptosis including mitochondrial cytochrome c release and apoptosomemediated activation of caspases evolved in early metazoans (Zmasek and Godzik, 2013;Chai and Shi, 2014;Green and Fitzgerald, 2016). Elevated levels of AChE expression induced by apoptogenic stressors and apoptosis inhibition by experimental reduction of AChE presence and/or catalytical activity have also been detected in insects (Knorr et al, 2020;Knorr et al, 2022) paralleling previous reports from studies with vertebrate cells. The molecular mechanisms underlying AChE's pro-apoptotic functions have not been revealed in any invertebrate species.…”
Section: Ache In Invertebrate Apoptosissupporting
confidence: 73%
See 2 more Smart Citations
“…Current knowledge suggests that complex regulation of apoptosis including mitochondrial cytochrome c release and apoptosomemediated activation of caspases evolved in early metazoans (Zmasek and Godzik, 2013;Chai and Shi, 2014;Green and Fitzgerald, 2016). Elevated levels of AChE expression induced by apoptogenic stressors and apoptosis inhibition by experimental reduction of AChE presence and/or catalytical activity have also been detected in insects (Knorr et al, 2020;Knorr et al, 2022) paralleling previous reports from studies with vertebrate cells. The molecular mechanisms underlying AChE's pro-apoptotic functions have not been revealed in any invertebrate species.…”
Section: Ache In Invertebrate Apoptosissupporting
confidence: 73%
“…Elevated AChE levels may also result from reduced degradation, as has been demonstrated in amyloid beta-stimulated murine neuroblastoma cells (Hu et al, 2003). While presence of AChE per se does not initiate apoptosis, elevated levels sensitize the induction of apoptosis under pathogenic or physiologically challenging conditions (Jin et al, 2004;Knorr et al, 2022). Some studies indicated that only particular splice variants of mammalian AChE induce apoptosis in the investigated cell types, such as N-AChE-S in cholinergic cortex neurons and glioblastoma cells (Toiber et al, 2008).…”
Section: Ache Promotes Apoptosismentioning
confidence: 99%
See 1 more Smart Citation